The Implementation of Library Services in A Digital School: A Case Study at SMAN 1 Geger Madiun - Kardi, Kardi; Sari, Dwi Eliana (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: The evolution toward "Digital Schools" has permanently repositioned school libraries as the potential nexus of the institutional information ecosystem. However, for libraries with established digital identities, the transition from analog-centric services to fully integrated digital ecosystems remains a complex institutional challenge. Purpose: This case study assesses the service models, adaptation strategies, and systemic obstacles involved in incorporating digital library services at SMAN 1 Geger Madiun, specifically focusing on its transition into a digitally unified institution. Methods: Utilizing a qualitative case study methodology, data were gathered through in-depth interviews, focus groups, and field observations involving librarians, educators, students, and IT personnel. Thematic analysis was applied within the framework of Calhoun’s Digital Transformation, focusing on interoperability, service adaptation, and long-term sustainability. Findings: The study indicates that the digital library model remains fragmented and "underdeveloped." A critical lack of interoperability exists between the school’s RFID system and the library's manual user-access protocols, preventing a unified ecosystem. Despite these hurdles, the library has implemented adaptable "dual-access" models (stationary and portable) and diversified procurement through grants and perpetual licenses. However, progress is significantly stalled by a deficit in human resource digital literacy and inadequate data protection frameworks. Originality/Value: The library's digital services still act as a separate entity from the school's digital ecosystem. This entails that the services offered by the library need to be integrated with the school's digital ecosystem. From an institutional perspective, this overwhelmingly points to the need for policies that prioritize an interdisciplinary approach to systems integration, the sustainability of personnel, and the protection of informational data.